Challenges in developing green skills in higher education: a narrative literature review - Norhana Binti Safee; Noor Mayafaraniza Binti Kosnan (Journal of Educational and Learning Studies, 2024)
The development of green skills in higher education, particularly within Technical and Vocational Education and Training (TVET), is confronted with several critical challenges that demand prompt solutions. The existing literature emphasizes the essential role of green skills in equipping graduates to meet the dynamic needs of contemporary industries and enhancing their employability. These skills are crucial for sustainability and adaptability in the workforce. However, multiple factors complicate the integration of green skills into TVET curricula. Firstly, there is a lack of clarity and consistency in defining green skills, which creates confusion among stakeholders, including students, educators, and employers. This ambiguity leads to varied interpretations and inconsistent emphasis on green skills across educational programs. Secondly, discrepancies in the perception of the importance and application of green skills between academia and industry result in a misalignment of educational practices with industry expectations. This gap hampers the effectiveness of green skill development in preparing students for real-world challenges. Moreover, pedagogical challenges such as large class sizes and a focus on summative assessments limit opportunities for personalized learning experiences and active engagement, which are vital for the effective teaching and assessment of green skills. Institutional barriers, including resource constraints and inflexible curricular structures, further exacerbate these challenges, particularly in the TVET context, where practical skill development is paramount. In conclusion, addressing these multifaceted challenges requires collaborative efforts to establish clear definitions of green skills, align educational curricula with industry demands, and innovate pedagogical strategies. By overcoming these obstacles, higher education institutions can significantly enhance their role in preparing graduates for a rapidly evolving global job market, thereby promoting sustainable economic growth and environmental stewardship.